The Effect of Gender on Consumer Satisfaction and Loyalty in Modern Retail Stores - Sri Maryanti; Febrian Humaidi Sukmana; Suharti Suharti; Faezal Faezal (SENTRALISASI, 2022)
This study aimed to determine whether there were differences in the satisfaction and loyalty of male and female consumers at the Alfamart Mujur branch of the retail store in East Praya. A total of 140 respondents participated, and the data analysis used was the MANOVA Test with SPSS 17. From the several hypotheses proposed, it was found that the three alternative hypotheses were rejected. In other words, there was no difference, either partially or simultaneously, between the satisfaction and loyalty of male consumers. - male and female. Based on these findings, Alfamart Branch Mujur must remain focused on developing consumer-oriented marketing and service strategies without the need to differentiate services or treatment for male and female consumers.